The impact of banking concentration on firm leverage in emerging markets - Farzin, Abadi; A. N., Bany Ariffin; Kokoszczynski, Ryszard; W. N., W. Azman Saini (Emerald Publishing Limited, 2016)
Purpose The purpose of this paper is to explore the impact of banking concentration on firm leverage in 21 major emerging countries from different geographical regions, controlling for firm determinant and macroeconomic determinant of firm leverage.